Multifunctional magnesium-organic framework doped biodegradable bone cement for antibacterial growth, inflammatory regulation and osteogenic differentiation. Issue 13 (10th March 2023) - Wang, B.; Chen, H.; Peng, S.; Li, X.; Liu, X.; Ren, H.; Yan, Y.; Zhang, Q.
Abstract : Mg-MOF doped CS/CC/DCPA biodegradable bone cement not only promotes osteogenic differentiation of BMSCs, but also has antibacterial and anti-inflammatory functions. In addition, the doped Mg-MOF also improves the compressive strength of bone cement. Abstract : Degradable bone cement has superior osteoconductivity and plasticity and is commonly used to treat defects greater than the critical-size. Magnesium gallate metal–organic frameworks (MOFs) (Mg-MOF), with antibacterial and anti-inflammatory properties, are doped into a composite cement composed of calcium sulfate, calcium citrate, and dicalcium hydrogen phosphate anhydrous (CS/CC/DCPA). The doping of the Mg-MOF slightly influences the microstructure and curing properties of the composite cement, with the mechanical strength of the cement displaying a significant increase from 27 to 32 MPa. Antibacterial tests reveal that the Mg-MOF bone cement has excellent antibacterial characteristics and can effectively inhibit bacterial growth in 4 h ( Staphyloccocus aureus survival rate <10%). Herein, lipopolysaccharide (LPS)-induced macrophage models are used to investigate the anti-inflammatory characteristics of composite cement. The Mg-MOF bone cement can regulate the inflammatory factors and polarization of macrophages (M1 and M2). In addition, the composite cement promotes cell proliferation and osteo-differentiation of mBMSCs, and the activity of alkaline phosphatase and calcium nodules are increased. The bone related transcription factor and specific proteins, such as runt-related transcription factor 2 (Runx2), bone morphogenetic protein 2, osteocalcin (OCN), osteopontin (OPN), and collagen type 1 (COL1), were highly expressed by the Mg-MOF bone cements. Therefore, Mg-MOF doped CS/CC/DCPA bone cement is multifunctional for bone repair, which will promote bone formation and avoid the infection of wounds, and it is suitable for use with non-load-bearing bone defects.